Analisis Pengaruh Perkebunan Kelapa Sawit Terhadap Perekonomian di Provinsi Sumatera Utara Tahun 2012-2020 - Noni Rozaini; Tinti Sriyani (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This study aims to determine how the influence of area, plantation production and labor on economic growth in North Sumatra Province. This study uses secondary data taken from the BPS of North Sumatra Province in 2012-2020. This study uses multiple linear regression analysis. The assumption test used is descriptive statistical analysis, normality test, autocorrelation test, multicollinearity and heteroscedasticity test. The entire data processing of this research uses the Eviews 9 analysis tool. The results of this study indicate that area has a positive and insignificant effect on the GRDP of North Sumatra, the plantation production variable has a positive but not significant effect on the GRDP of North Sumatra and the labor variable has a positive and significant effect on GRDP North Sumatra.